Study Eksploratif Tentang Kekerasan terhadap Perempuan Dalam Rumah Tangga di Kabupaten Indramayu Jawa Barat - Erni Sulastri; Sofia Retnowati (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2003)
The current study explored the main themes, especially psychlogical themes,  which occur in the domestic violence phenomena among women in Indramayu , West Java. Social census often show Indramayu as an area where statistics of prostitutions, including teens prostitution, are high, beside the divorced rate. Prostitution is often considered as a form of violence towards women. Yet, domestic violence, which is expected to occur at the societal level in Indramayu remain unexplored.  The study used qualitative method namely focus group discussion, interview, observation and open ended questionaire. The finding of this study shows that over 90% respondents had experienced violent treatment, in any form, in their marriage. This study  finding is also in line with other studies on domestic violence which show at least four type of violence,  listed as economic, psychological, physical and sexual violence. Some sub themes can be mapped out from the data, including the underlying factors which trigger violence behavior from the husband, different form reactions to violence acts, various conseqences of domestic violence on the part of the women/wife. Some cases of violence showed that husbands were sometimes involved in encouraging women to get engaged in prostitutions. It was also found that “accepting” mentality a sense of hopelessness existed among Indramayu women in facing domestic violence.Key Words: Domestic violence, Violence towards women,  Indramayu- West Java.